Synthesis and antimicrobial activity of novel (3,5-dichloro-4-((5-aryl-1,3,4-thiadiazol-2-yl)methoxy) phenyl) aryl methanones - V. Srinivasa Murthy, B. K. Manuprasad, S. Shashikanth (Journal of Applied Pharmaceutical Science)
A series of novel (3,5-dichloro-4-((5-aryl-1,3,4-thiadiazol-2-yl)methoxy)phenyl) aryl methanones (10a-f), were synthesized by condensing 2-chloromethyl-5-aryl-1,3,4-thiadiazole (9a-c) with aryl(3,5-dichloro-4-hydroxyphenyl) methanones (4a-b) using TBAB and K2CO3. The chemical structure of the newly synthesised compounds was characterized by analytical and spectral (IR, 1H NMR, and LC-MS) methods. The title compounds were screened for qualitative (zone of inhibition) and quantitative antimicrobial activity (MIC) by agar well and microbroth dilution technique, respectively. Among the synthesized compounds in the series, the compound 10f was found to exhibit significant antibacterial activity at lower concentration, against Gram positive bacteria such as Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, and Bacillus cereus and Gram negative bacteria such as E.coli, Pseudomonas aeruginosa, Salmonella typhi, and Klebsiella pneumoniae. The rest of the analogues in the series displayed moderate antimicrobial activity when compared to the standard positive controls gentamicin and nystatin.
Keywords: 2,6-dichlorophenol,aryl (3,5-dichloro-4-hydroxyphenyl)methanone,(3,5-dichloro-4-((5-aryl-1,3,4-thiadiazol-2-yl)methoxy)phenyl) aryl methanones.